Experimental Study on Seismic Compression of Chinese Loess under Cyclic Direct Simple Shear Testing - Qiang Wang; Zhe Zhang; Shengjun Shao; Qian Yang (Advances in Civil Engineering)
Seismic compression is the accumulation of contractive volumetric strains in unsaturated soil from earthquake shaking. For Chinese loess, the behavior of seismic compression is extremely significant and has been recognized in historical earthquakes. As a main technical mean, dynamic triaxial apparatus has been employed to study the seismic compressibility of loess for a long time. However, dynamic simple shear apparatus is superior to dynamic triaxial apparatus in modeling the real stress condition of soil under earthquake. Meanwhile, dynamic triaxial apparatus could not measure the volumetric strain of unsaturated loess precisely. A series of cyclic compression tests are hereby performed on unsaturated and intact loess by the new cyclic direct simple shear device developed in Xi’an University of Technology. The properties of cyclic compression of loess specimens are analyzed under the combined conditions of four water contents, four vertical stresses, and six shear strains. The test results reveal that the volumetric strain is constantly compacted through the process of cyclic load-unloading and is much larger during loading half-cycle than unloading half-cycle. It has been found that the cyclic compressibility of loess is dependent upon density, water content, confining pressure, shear strain (or stress), and cycles. An empirical formula to estimate the increment of cyclic volumetric strain per cycle is expressed in terms of the amplitude of shear train, dry density, water content, and vertical stress. Moreover, a simplified evaluation procedure is proposed for the probable settlements of loess deposits subjected to earthquake shaking.